1976
DOI: 10.1021/ja00423a039
|View full text |Cite
|
Sign up to set email alerts
|

Ozonization of organic substrates. Hydrotrioxide formation and decomposition to give singlet oxygen

Abstract: In the net sense, chemical and electrochemical oxidations of the ions [Ru(bpy)2(NFl2CH2R)2]2+ (NH2CH2R = allylamine, benzylamine, and zi-butylamine) occur by dehydrogenation at the amine ligands giving the corresponding bis(nitrile) complexes, [Ru(bpy)2(N=CR)2]2+. The reactions appear to proceed by initial oxidation of Ru(II) to Ru(III), followed by a series of stepwise dehydrogenation reactions which occur via imine intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 14 publications
(14 reference statements)
2
35
0
1
Order By: Relevance
“…Price and co-workers [68] proposed the so-called "insertion" mechanism, according to which ozone is inserted into the α-C-H bonds at the first step through 1,3-dipolar addition, thus forming unstable HTO. This mechanism was also supported by the data of Erickson and Bailey [2,67,69], Murray and coworkers [70], who measured the activation parameters of the decomposition of a series of HTO, obtained by the ozonolysis of some ethers. Giamalva and co-workers [71] summarized the possible mechanisms known today, i.e.…”
Section: Etherssupporting
confidence: 61%
“…Price and co-workers [68] proposed the so-called "insertion" mechanism, according to which ozone is inserted into the α-C-H bonds at the first step through 1,3-dipolar addition, thus forming unstable HTO. This mechanism was also supported by the data of Erickson and Bailey [2,67,69], Murray and coworkers [70], who measured the activation parameters of the decomposition of a series of HTO, obtained by the ozonolysis of some ethers. Giamalva and co-workers [71] summarized the possible mechanisms known today, i.e.…”
Section: Etherssupporting
confidence: 61%
“…[27][28][29][30] This splitting was previously assigned to the presence of two hydrotrioxide forms with OOOH bonded either intramolecularly or intermolecularly 9-12:…”
Section: Resultsmentioning
confidence: 99%
“…Erickson et al (1968) identified tert-butyl acetate, tert-butyl formate and tert-butyl alcohol as ETBE ozonation byproducts. According to Bailey and Lerdal (1978), two types of initial attack of ozone on ethers take place and lead to the formation of hydrotrioxide intermediates (identified by Stary et al, 1976). The most important, the 1,3-dipolar insertion would be activated by the least acidic hydrogen in the alphaposition from the ether group (Price and Tumolo, 1964;Bailey and Lerdal, 1978;Giamalva et al, 1986).…”
Section: And the Year 2000 By A Quadrupling Of The American Consumptmentioning
confidence: 99%